Culturally Grounded Module Development for Barayti at Baryasyon ng Wika: Integrating Student Perspectives Toward Linguistic Sustainability - Cabiles, Neña Vanessa A. (Journal of Qualitative Research in Education, 2025)
This study developed and evaluated a culturally grounded instructional module for the course Barayti at Baryasyon ng Wika, integrating student perspectives to strengthen comprehension of Filipino language variation and promote linguistic sustainability. Drawing on persistent gaps in instructional materials and the documented difficulty of students in distinguishing key sociolinguistic concepts, the research employed a qualitative descriptive design to capture authentic learner experiences, cultural interpretations, and instructional insights. Data were gathered from purposively selected students and teacher-evaluators through semi-structured interviews, written reflections, and narrative reviews. Reflexive thematic analysis revealed three major findings: (1) students experience significant conceptual ambiguity when differentiating categories such as dialect, sociolect, register, and idiolect, especially when examples are abstract or decontextualized; (2) the culturally grounded module substantially improved comprehension by providing sequenced explanations, contextualized examples, and familiar linguistic scenarios that bridge theoretical concepts with real-life language use; and (3) both learners and teachers affirmed the module’s high clarity, instructional coherence, and cultural resonance, noting its effectiveness in reinforcing awareness of linguistic sustainability and Filipino identity. The study demonstrates that culturally anchored materials not only enhance academic understanding but also cultivate positive attitudes toward Filipino linguistic diversity. These findings underscore the necessity for localized, research-based instructional resources that respond to the cognitive and cultural needs of Filipino learners. The module serves as a pedagogically robust and culturally meaningful contribution to Filipino language education, supporting efforts toward linguistic vitality amid shifting societal and technological landscapes.